A Nucleotide-Binding Domain Leucine-Rich Repeat Gene Regulates Plant Growth and Defense Against Chewing Herbivores - Chen Qiu; Xiaochen Jin; Yumiao Zhao; Peng Kuai; Yonggen Lou (Plants)
Plant nucleotide-binding leucine-rich repeat immune receptor genes (NLRs) play an important role in plant defenses against pathogens, pathogenic nematodes, and piercing–sucking herbivores. However, little is known about their functions in plant defenses against chewing herbivores. Here, we identified a plasma membrane-localized coiled-coil-type NLR protein, OsPik-2-like, whose transcript levels were induced by the infestation of rice leaf folder (LF, Cnaphalocrocis medinalis) larvae, and by treatment with mechanical wounding. Knocking out OsPik-2-like in rice increased the LF-induced levels of jasmonic acid (JA) and jasmonoyl–isoleucine (JA-Ile), the activity of trypsin protease inhibitors (TrypPIs), and the basal levels of some flavonoids, which in turn decreased the performance of LF larvae. Moreover, knocking out OsPik-2-like reduced plant growth. These findings demonstrate that OsPik-2-like regulates the symbiosis between rice and LF by balancing plant growth and defense.